Investigation on steering of ultrarelativistic $$e^{± }$$ e ± beam through an axially oriented bent crystal - L. Bandiera (European Physical Journal C: Particles and Fields, 2021)
Abstract An investigation on stochastic deflection of high-energy charged particles in a bent crystal was carried out. In particular, we investigated the deflection efficiency under axial confinement of both positively and negatively charged particles as a function of the crystal orientation, the choice of the bending plane, and of the charge sign. Analytic estimations and numerical simulations were compared with dedicated experiments at the H4 secondary beam line of SPS North Area, with 120 GeV/c electrons and positrons. In the work presented in this article, the optimal orientations of the plane of bending of the crystal, which allow deflecting the largest number of charged particles using a bent crystal in axial orientation, were found.